Membentuk Karakter Unggul Dan Kreativitas Anak Sekolah Dasar Dalam Mendukung Desa Mandiri - Supartono; Neli Ferawati; Herman Hermawan; Ahmad Nur Asrofi; Agus Darmadi; Ami Nurhidayah; Siti Nurannisa; Daimah Dianawati; Moohammad Rasyah Aufa (CV. ITTC INDONESIA, 2024)
This community service program aims to develop superior character and creativity in elementary school children to support the realization of an independent village in Jatiwangi Village, West Cikarang, Bekasi. Using a Participatory Action Research (PAR) approach, the program focuses on three main aspects: creating literacy corners and ecoprint, character education, and maintaining a clean and healthy school environment. The methods used include participatory observation, interviews, and activity documentation. Results show an increase in students' reading interest, strengthening of positive values, and improved environmental awareness. The program successfully fostered a spirit of mutual cooperation and community ownership towards education and their environment. The main challenge faced was the time needed to change habits and mindsets. However, with a consistent approach and good collaboration between the service team, schools, and community, positive changes began to emerge. This program has laid a strong foundation for efforts to realize Jatiwangi Village as a sustainable independent village.